Effect of Jackfruit Leaf Extract (Artocarpus heterophyllus) on Sitophilus oryzae Mortality and Rice Quality - Astija Astija; Evi Wardani; Vita Indri Febriani; Fatma Dhafir (Scientifica)
Sitophilus oryzae is an insect pest known for its destructive impact on rice crops. Chemical pesticides continue to be employed for the prevention of Sitophilus oryzae. The aforementioned phenomenon exerts adverse effects, notably in the form of human intoxication. Hence, one alternate approach to address the issue involves utilizing a preparation derived from the leaves of the jackfruit tree. The leaves of the jackfruit tree are known to possess many bioactive compounds such as flavonoids, saponins, and tannins, which have insecticidal properties. Hence, the objectives of this study are to investigate the impact of jackfruit leaf extract on the mortality rate of rice insects and to evaluate the quality of rice. The study was carried out in the Biology Laboratory of the Faculty of Education and Teacher Training at the Tadulako University. The study employed a research strategy known as a completely randomized design (CRD), which included five treatments. Each treatment was repeated in four biological and ten technical replicates. The treatments were as follows: treatment A served as the control and involved the use of Bestrin forte, treatment B involved the application of a 10% jackfruit leaf extract, treatment C involved the application of a 20% jackfruit leaf extract, treatment D involved the application of a 30% jackfruit leaf extract, and treatment E involved the application of a 40% jackfruit leaf extract. Every treatment was administered through spraying to all ten insects and that was repeated four times. The data collected were subjected to analysis using analysis of variance (ANOVA) and supported by the SPSS-25 software. The findings of the study indicated that the application of jackfruit leaf extract (Artocarpus heterophyllus) at specific time intervals (20th, 40th, and 60th minutes) resulted in a noteworthy impact on the death rate of rice beetles. Furthermore, the extracts successfully preserved the olfactory attributes of the rice, ensuring its quality. Nevertheless, their ability to uphold the standard of the rice in relation to its color and flavor was inadequate. The efficacy of the jackfruit leaf extract in eradicating rice bugs was found to be highest when applied at a concentration of 40%.